Effectiveness of manual therapy for pain and self-reported function in individuals with patellofemoral pain: Systematic review and meta-analysis - Eckenrode, B. J.; Kietrys, D. M.; Parrott, J. S. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
Study Design: Systematic literature review with meta-analysis. Background: Management of patellofemoral pain (PFP) may include the utilization of manual therapy (MT) techniques to the patellofemoral joint, surrounding soft tissues, and/or lumbopelvic region. Objectives: To determine the effectiveness of MT, used alone or as an adjunct intervention, compared to standard treatment or sham for reducing pain and improving self-reported function in individuals with PFP. Methods: An electronic literature search was conducted in the PubMed, Ovid, Cochrane Central Register of Controlled Trials, and CINAHL databases for studies investigating MT for individuals with PFP. Studies published through August 2017 that compared MT (local or remote to the knee), used alone or in combination with other interventions, to control or sham interventions were included. Patient-reported pain and functional outcomes were collected and synthesized. Trials were assessed via the Cochrane risk-of-bias tool, and a meta-analysis of the evidence was performed. Results: Nine studies were included in the review, 5 of which were rated as having a low risk of bias. The use of MT, applied to the local knee structure, was associated with favorable short-term changes in self-reported function and pain in individuals with PFP, when compared to a comparison (control or sham) intervention. However, the changes were clinically meaningful only for pain (defined as a 2-cm or 2-point improvement on a visual analog scale or numeric pain-rating scale). The evidence regarding lumbopelvic manipulation was inconclusive for pain improvement in individuals with PFP, based on 3 studies. Conclusion: The data from this review cautiously suggest that MT may be helpful in the short term for decreasing pain in patients with PFP. Several studies integrated MT into a comprehensive treatment program. Changes in self-reported function with the inclusion of MT were shown to be significant, but not clinically meaningful. The limitations in the studies performed to date suggest that future research should determine the optimal techniques and dosage of MT and perform longer follow-up to monitor long-term effects.